2015
DOI: 10.1128/genomea.00828-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Strain ATCC 33958, Reported To Be Elizabethkingia miricola

Abstract: We report the draft genome of Elizabethkingia strain ATCC 33958, which has been classified as Elizabethkingia miricola. Similar to other Elizabethkingia species, the ATCC 33958 draft genome contains numerous β-lactamase genes. ATCC 33958 also harbors a urease gene cluster which supports classification as E. miricola.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This isolate was reclassified as E. meningoseptica in the same study that misidentified E. miricola isolate CIP108653 as E. meningoseptica based on 16S rRNA sequences (Bernardet et al., 2005). Given the changes in nomenclature and the sometimes challenging identification of Elizabethkingia isolates (de Carvalho Filho, Marson, & Levy, 2017; Han et al., 2016; Matyi, Hoyt, Ayoubi‐Canaan, Hasan, & Gustafson, 2015; Rahim, Gupta, & Aggarwal, 2018), it cannot be excluded that some historic descriptions of bacterial infections similar to the condition described here (Chung, 1990; Green et al, 1999; Mauel, Miller, Frazier, & Hines, 2002; Olson, Gard, Brown, Hampton, & Morck, 1992; Taylor, Simmonds, & Loeffler, 1993) are in fact related to E. miricola infection. This would make E. miricola a more important amphibian pathogen than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…This isolate was reclassified as E. meningoseptica in the same study that misidentified E. miricola isolate CIP108653 as E. meningoseptica based on 16S rRNA sequences (Bernardet et al., 2005). Given the changes in nomenclature and the sometimes challenging identification of Elizabethkingia isolates (de Carvalho Filho, Marson, & Levy, 2017; Han et al., 2016; Matyi, Hoyt, Ayoubi‐Canaan, Hasan, & Gustafson, 2015; Rahim, Gupta, & Aggarwal, 2018), it cannot be excluded that some historic descriptions of bacterial infections similar to the condition described here (Chung, 1990; Green et al, 1999; Mauel, Miller, Frazier, & Hines, 2002; Olson, Gard, Brown, Hampton, & Morck, 1992; Taylor, Simmonds, & Loeffler, 1993) are in fact related to E. miricola infection. This would make E. miricola a more important amphibian pathogen than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…While a comprehensive comparison of Elizabethkingia genomes is forthcoming, this preliminary analysis suggested that E. miricola is most similar to genomospecies 2, while both E. anophelis and E. endophytica are most similar to genomospecies 1. The 16S rRNA sequence from the recently published draft genome of Elizabethkingia strain ATCC 33958 ( 10 ) was an exact match to the gene from Elizabethkingia genomospecies 3.…”
Section: Genome Announcementmentioning
confidence: 92%
“…Canu was chosen because it provides higher assembly sequence identity than competing long-read assemblers, such as miniasm (Koren et al, 2017). Minimum overlap length was 500 bp and suggested genome size was 3.8 Mb and 4.5 Mb for E. meningoseptica KC1913 (Matyi et al, 2013), and E. bruuniana ATCC 33958 (Matyi et al, 2015), respectively.…”
Section: Methodsmentioning
confidence: 99%